2004
DOI: 10.1161/01.cir.0000144457.55518.e5
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic and Adipogenic Potential of Microvascular Pericytes

Abstract: Background-Previous studies have shown that pericytes can differentiate into osteoblasts and form bone. This study investigated whether pericytes can also differentiate into chondrocytes and adipocytes. Methods and Results-Reverse transcription-polymerase chain reaction demonstrated that pericytes express mRNA for the chondrocyte markers Sox9, aggrecan, and type II collagen. Furthermore, when cultured at high density in the presence of a defined chondrogenic medium, pericytes formed well-defined pellets compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
305
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(319 citation statements)
references
References 32 publications
7
305
1
6
Order By: Relevance
“…With regards to adipogenesis, Uezumi et al showed that PDGFRα+ MSCs, completely distinct from PDGFRβ+ pericytes, are responsible for adipogenesis in skeletal muscles and a balance between satellite cell-derived myofibres and PDGFRα+ cells maintain muscle homeostasis (Uezumi et al, 2010). However, differentiation of pericytes into adipocytes has been documented (Birbrair et al, 2013a;Farrington-Rock et al, 2004;Tang et al, 2008), and the differences between studies may well be dependent on the muscle condition and the subsequent interaction between cell types in the context of muscle injury.…”
Section: Muscle Injurymentioning
confidence: 99%
See 3 more Smart Citations
“…With regards to adipogenesis, Uezumi et al showed that PDGFRα+ MSCs, completely distinct from PDGFRβ+ pericytes, are responsible for adipogenesis in skeletal muscles and a balance between satellite cell-derived myofibres and PDGFRα+ cells maintain muscle homeostasis (Uezumi et al, 2010). However, differentiation of pericytes into adipocytes has been documented (Birbrair et al, 2013a;Farrington-Rock et al, 2004;Tang et al, 2008), and the differences between studies may well be dependent on the muscle condition and the subsequent interaction between cell types in the context of muscle injury.…”
Section: Muscle Injurymentioning
confidence: 99%
“…In vitro tri-lineage differentiation of pericytes into mesenchymal cell types has been welldocumented (Crisan et al, 2012;Crisan et al, 2008;Farrington-Rock et al, 2004), and efforts to translate into in vivo transplantation models are underway. CD146+/CD34-/CD45-/CD56-pericytes from human skeletal tissue have exhibited osteo-, adipo-, chondro-and myogenic potential.…”
Section: Bone Fat and Cartilagementioning
confidence: 99%
See 2 more Smart Citations
“…Pericytes are contractile cells that envelop the endothelial cells of capillaries and postcapillary venules [100]. Besides the function specifically linked to the vasculature, it was reported that they have oligopotential capacity, being able to differentiate into osteocytes, chondrocytes, and adipocytes [101,102]. Results on the myogenicity of pericytes are not homogeneous, varying from one laboratory to another.…”
Section: Heterodox Myogenic Cellsmentioning
confidence: 99%